Perancangan Sistem E-Commerce Produk Kerajinan Bambu di Desa Air Kenari, Kecamatan Teluk Mutiara Kabupaten Alor - Jon Idrison Molina; Lasarus Pelipus Malese; Deni Wileksi Nomate (Peneliti.net, 2022)
Today's very rapid technological developments have been utilized in various fields of life, not to be left behind in the economic field, especially in online sales (e-commerce). E-Commerce is an information technology medium that can facilitate online trading without physical meetings between sellers and buyers. With this e-commerce technology, it can minimize spending time, effort and costs to market a product. The system that has been produced can use the e-commerce system to help sell bamboo craftsman products quickly and efficiently